2017
DOI: 10.1038/jp.2016.245
|View full text |Cite
|
Sign up to set email alerts
|

Major anomalies and birth-weight influence NICU interventions and mortality in infants with trisomy 13 or 18

Abstract: Objective to describe neonatal intensive care unit (NICU) medical interventions and NICU mortality by birth weight and major anomaly types for infants with trisomy 13 (T13) or 18 (T18). Study Design retrospective cohort analysis of infants with T13 or T18 from 2005–12 in the Pediatrix Medical Group. We classified infants into 3 groups by associated anomaly type: neonatal surgical, non-neonatal surgical, and minor. Outcomes were NICU medical interventions and mortality. Results 841 infants were included fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 35 publications
2
19
0
1
Order By: Relevance
“…Male gender, cardiovascular abnormalities, prematurity, and very low birth weight negatively affect survival. 6,8,24,28 In keeping with those studies, we found that survival rates were significantly lower in infants with birth weight of <2,000 g and who had more than two anomalies (p ¼ 0.001).…”
Section: Discussionsupporting
confidence: 89%
“…Male gender, cardiovascular abnormalities, prematurity, and very low birth weight negatively affect survival. 6,8,24,28 In keeping with those studies, we found that survival rates were significantly lower in infants with birth weight of <2,000 g and who had more than two anomalies (p ¼ 0.001).…”
Section: Discussionsupporting
confidence: 89%
“…Recently, more infants are receiving medical interventions, and survival for more than a year is not uncommon, leading to a recommendation to avoid calling these conditions “lethal.” 1 We have previously reported that parents who lived with children with T13-18 experienced significant emotional and financial hardships, but that they also reported many positive experiences. 24…”
Section: Introductionmentioning
confidence: 99%
“…1 We have previously reported that parents who lived with children with T13-18 experienced significant emotional and financial hardships, but that they also reported many positive experiences. [2][3][4] T13-18 are heterogeneous conditions: some children will die within weeks, despite attempts at life-saving interventions, while others may survive for several months or years, even with comfort care. Medical or surgical interventions, which may sometimes be beneficial, can also at times be a burden.…”
Section: Introductionmentioning
confidence: 99%
“…T21 is a discretely coded diagnosis. As described in our prior work, 8 we manually reviewed all diagnoses and categorized major anomalies similar to reports from the Vermont Oxford Network 9 and National Institute of Child Health and Development (NICHD) Neonatal Research Network. 10 If an infant had more than one anomaly, each was coded separately.…”
Section: Methodsmentioning
confidence: 99%